On Uniformly Convexity Of Orlicz Spaces - AZHARY MASTA (NIM : 20111035); Pembimbing : Wono Setya Budhi, Ph.D, AL
Orlicz Spaces has introduction by Z.W Rirnbaum and W. Orlicz since 1931. Orlicz spaces one of Banach spaces which extensions from spaces. As extension from spaces, there are much characteristic of spaces valid for Orlicz spaces. Carothers has been proved is Banach spaces. Else, Carothers has been proved, for every uniformly convex spaces is strictly convex, but converse is not true. On this paper, we will define new norm for Orlicz space and show equivalence with another norm on orlicz spaces . Besides, we will observe condition for uniformly convex, which convexity of Orlicz spaces we define from norm on this papers. Furthermore, we will observe condition for strictly convex if only if uniformly convex.